1998
DOI: 10.1139/x98-114
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature but not elevated CO2 affects long-term patterns of stem diameter and height of Douglas-fir seedlings

Abstract: Global climatic change may impact forest productivity, but data are lacking on potential effects of elevated CO2 and temperature on tree growth. We determined changes in shoot growth for Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) seedlings exposed to ambient or elevated CO2 ( µmol·mol-1), and ambient or elevated temperature . Seedings were grown for 4 years (three complete growing seasons) in outdoor, sunlit chambers. In each season, height growth was initiated earlier and, in two seasons, ceased earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 0 publications
1
54
0
Order By: Relevance
“…This discrepancy might be caused by the different research conditions and plant species used. In the experiment with Douglas-fir (Olszyk et al 1998;Olszyk et al 2003), seedlings were exposed to warming for 4 years under non-controlled light conditions, whereas in the present study, P. purpurea seedlings were exposed for 4 years under controlled light conditions. Low-light conditions could potentially influence more resource allocation to the shoot to increase the ability of light competition (Marfo and Dang 2009).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This discrepancy might be caused by the different research conditions and plant species used. In the experiment with Douglas-fir (Olszyk et al 1998;Olszyk et al 2003), seedlings were exposed to warming for 4 years under non-controlled light conditions, whereas in the present study, P. purpurea seedlings were exposed for 4 years under controlled light conditions. Low-light conditions could potentially influence more resource allocation to the shoot to increase the ability of light competition (Marfo and Dang 2009).…”
Section: Discussionmentioning
confidence: 83%
“…The results presented here are in disagreement with the previous reports on effects of elevated temperature on plant in the presence of competition. For example, Olszyk et al (1998) showed that elevated temperature reduced height growth but increased diameter in Douglas-fir seedlings grown in a stand (Olszyk et al 1998). Olszyk et al (2003) found elevated temperature decreased allocation of biomass from leaves and increased allocation to stems for Douglas-fir seedlings grown in the presence of competition.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of warming on tree or seedling growth have been previously studied on Scots pine (Pinus sylvestris; Domisch et al 2002;Kilpeläinen et al 2005), Douglas-fir (Pseudotsuga menziesii; Olszyk et al 1998Olszyk et al , 2003 (2001) found that warming had no significant effect on height growth but increased ring width by 19% in Scots pines during an experimental treatment spanning 6 years. In A. faxoniana seedlings, short-term warming increased height growth but had no effect on diameter (Hou et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these findings were obtained from experiments with young seedlings grown without competition. In addition, elevated temperature reduced height growth but increased diameter in Douglas-fir seedlings when grown in competition under non-controlled light conditions (Olszyk et al 1998). However, we used seedlings grown in even-aged monospecific stands with controlled light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation